Perceived Value in Consumer Purchasing Decisions on Facebook Ads: A Study on Millennial Generation in Cikarang - Rabbani, Muhammad Amru; Dwianto, Agung Surya (Jurnal Ilmiah Global Education, 2025)
This study aims to examine how perceived value is formed in consumer purchasing decisions for products offered through Facebook Ads, especially for the Millennial Generation in Cikarang City. Using a qualitative approach with a case study design, data was collected through interviews with informants who are active Facebook users who have purchased products through Facebook Ads. The results of the analysis show that perceived value is formed from the relationship between perceived benefits and sacrifices that are taken into consideration, such as the visualization of advertisements that trigger initial consumer interest, but on the other hand, concerns about the risk of delivery and actual product mismatches are the main sacrifice. Direct and transparent interaction with the seller via text message is proven to overcome these concerns. This builds trust and increases consumer confidence to transact. Other users' engagement with ads and the frequency with which they appear also contribute to improving consumers' perceptions of credibility and social recognition. Although consumers make comparisons in e-commerce with more competitive prices, the ease of transactions and the convenience of interacting with sellers are crucial factors that strengthen consumers to make purchasing decisions. This study enriches the qualitative understanding of the formation of consumer perceived value in online shopping through Facebook ads, as well as the role of personalized interactions that can mitigate risk.